OC-087 Frequency of Health Risk Behaviours in Young People With Inflammatory Bowel Disease. (17th August 2016) - Brooks, AJ; Rowse, G; Peach, EJ; Ryder, A; Narula, P; Corfe, BM; Norman, P; Lobo, AJ
Abstract : Introduction: Young people (YP) with any chronic illness are 3 times more likely to engage in health risk behaviours (HRBs) than healthy peers. 1 HRBs are a leading cause of morbidity and mortality, and are associated with poor self-management skills in adulthood. The aim of this study was to investigate the frequency of HRBs in YP with inflammatory bowel disease (IBD). Methods: YP aged 16–22 years with a confirmed diagnosis of IBD were recruited from a paediatric and adult IBD centre. Participants completed The Youth Risk Behaviour Survey (YRBS)–adapted, with demographic, disease and treatment-related data. Results: 121 patients were studied (75 (62%) CD, 39 (32%) UC, 7 (6%) IBDU), median age 19 years (range 16–22 years). Eight HRBs were identified including; 1) daily smoking in 15/117 (13%); 2) current alcohol misuse in 58/117 (49%); 3) current cannabis use in 12/117 (10%); 4) current use of other illegal drug in 20/121 (17%) with 39/118 (33%) offered, given or sold illegal drugs in the preceding 12 months; 5) previous sexual activity in 71/118 (59%), of whom 25/71 (35%) ≥4 previous sexual partners and 40/71 (56%) without condom use; 6) violent acts with physical fights in 8/118 (7%) and forced sexual intercourse in 5/118 (4%); 7) drink driving in 6/119 (5%) and texting whilst driving 14/118 (12%); 8) suicidal ideation in 9/118 (9%) and attempted suicide in 2/118 (2%). Of these HRBs, males were significantly more likely to participate in current illegal drug use (14/60 vs. 6/61) ( P = 0.02) and drink driving (6/59 vs. 0/59) ( P = 0.03). YP aged ≥19-22years were significantly more likely to participate in current illegal drug use (15/65 vs 5/56) ( P = 0.05), ≥4 sexual partners (21/45 vs. 4/26) ( P = 0.01), without condom use (31/45 vs. 9/26) ( P = 0.007) and to text whilst driving (13/64 vs. 1/54) ( P = 0.003) compared to YP aged 16- <19 years. Conclusion: In YP with IBD high levels of alcohol misuse and illegal drug use are observed compared to other chronic health conditions and healthy peers. 1 Clinician awareness of HRBs is vital for both paediatric and adult healthcare providers, with specific YP training for discussion of HRBs needed. Research is needed to understand factors which predispose YP with IBD to participate in HRBs, the impact on disease severity, and possible related outcomes such as psychological distress/morbidity that may have significant long-term health economic implications. Reference: 1 Suris JC, et al. Paediatrics 2008; 122 (5):e113–elll8. Disclosure of Interest: None Declared